Development Of New Organic Wood Paints With Lignin As Additive - Mustapha, Asniza (2011)
Lignin has been used as additive in preparation of the new organic paints. Soda lignin was extracted from black liquor of soda-AQ (anthraquinone) pulping of oil palm empty fruit bunch (EFB) fibers by 20% sulfuric acid precipitation. Two different types of azo pigment namely, phenyl-azo-2-naphthol and 4-Hydroxyphenylazo-3-N-(4-hydroxyphenyl)maleimide were synthesized by azo coupling reaction. Phenyl-azo-2-naphthol which was represented as aromatic azo pigment was produced from the reaction of diazonium salt (phenyldiazonium chloride) with pure 2-naphthol as the coupling agent whereas a new heterocyclic coupling agent namely, N-(4-hydroxy-phenyl)maleimide was synthesized by the reaction of maleic anhydride and p-aminophenol in the presence of di-phosphorus pentoxide (P2O5) as a catalyst.